Modal Mutu Pendidikan SD Muhammadiyah Condongcatur Yogyakarta - Salama, Heti; Taufik, Ahmad; Ramadhani, Khadafi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Islamic teachings elaborate on a broad, comprehensive scope, or can maintain relationships with other people. The criteria for the process of human creation is a divine gift regarding the noble mission of humans as caliphate when they are on this earth. Improving the quality of the credibility of SD Muhammadiyah always follows innovating according to the planning of the program form by setting strategic dialogue steps to improve quality. The way in which human resource development is carried out is based on various processes, such as recruitment and placement, welfare, development, career paths, both quality improvement, coaching, monitoring and evaluation of educators and can also be accommodated by education staff.